AKUNTABILITAS PENGELOLAAN KEUANGAN YAYASAN YUSUF ARIMATEA PALANGKA RAYA - Yesika Yanuarisa (Universitas Palangka Raya, 2020)
This study aims to determine the phenomenon of financial management of Yayasan Yusuf Arimatea in Palangka Raya in the observation year of 2019. The research method uses a qualitative method with a phenomenological approach to reveal the meaning of financial management of Yayasan Yusuf Arimatea Palangka Raya. Data collection techniques are done through interviews, observation and documentation. The results showed that the accountability of the financial reporting of Yayasan Yusuf Arimatea Palangka Raya had been carried out in accordance with generally accepted accounting standards. Evidenced by the existence of financial statements that have been made, which states that there is accountability to the GKE Resort Assembly Palangka Raya Hulu. The meaning of grieving for the bereaved family shows horizontal accountability by the trustees of the foundation to the Church and members of the Church as partners in the ministry.